(untitled) - Vrabelova, Lucia (Doprava a spoje, 2005)
This article deals with application of Monte Carlo method in option pricing, especially europian call stock option. Using Monte Carlo method we simulate course of corresponding stock price. We keep the required number of iterations. Using the last stock prices we calculate the prices of call option, their discounted average represent the Monte Carlo estimation of the option price. Comparing this price with the real option price we are able to determine an error of the estimate.